2012
DOI: 10.1007/s00355-011-0638-y
|View full text |Cite
|
Sign up to set email alerts
|

A counterexample to a conjecture of Schwartz

Abstract: In 1990, motivated by applications in the social sciences, Thomas Schwartz made a conjecture about tournaments which would have had numerous attractive consequences. In particular, it implied that there is no tournament with a partition A, B of its vertex set, such that every transitive subset of A is in the out-neighbour set of some vertex in B, and vice versa. But in fact there is such a tournament, as we show in this paper, and so Schwartz' conjecture is false. Our proof is non-constructive and uses the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…8 Another prominent Condorcet extension-the tournament equilibrium set (Schwartz, 1990)-was conjectured to satisfy SSP and monotonicity for almost 20 years. This conjecture was recently disproved by Brandt et al (2013). In fact, it can be shown that the tournament equilibrium set as well as the related minimal extending set (Brandt, 2011) can be For generalized strategyproofness as defined by Nehring (2000) (see Remark 6), the second condition is not required and every coarsening of a strategyproof SCF is strategyproof.…”
Section: The Resultsmentioning
confidence: 99%
“…8 Another prominent Condorcet extension-the tournament equilibrium set (Schwartz, 1990)-was conjectured to satisfy SSP and monotonicity for almost 20 years. This conjecture was recently disproved by Brandt et al (2013). In fact, it can be shown that the tournament equilibrium set as well as the related minimal extending set (Brandt, 2011) can be For generalized strategyproofness as defined by Nehring (2000) (see Remark 6), the second condition is not required and every coarsening of a strategyproof SCF is strategyproof.…”
Section: The Resultsmentioning
confidence: 99%
“…In the tournament of Figure 1, TEQ coincides withT C. Schwartz conjectured that every tournament admits a unique minimal TEQ-retentive set. This conjecture was recently disproved by a non-constructive argument using the probabilistic method (Brandt et al, 2012). While this proof showed the existence of a counter-example, no concrete counterexample (or even the exact size of one) is known.…”
Section: Retentive Setsmentioning
confidence: 98%
“…As was shown by Laffond et al (1993a) and Houy (2009a,b), TEQ satisfies any one of a number of important properties such as monotonicity if and only if Schwartz's conjecture holds. Brandt et al (2012) recently disproved Schwartz's conjecture by showing the existence of a counter-example of astronomic proportions. The interest in TEQ and retentiveness in general, however, is hardly diminished as concrete counter-examples to Schwartz's conjecture have never been encountered, even when resorting to extensive computer experiments (Brandt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 Schwartz (1990) showed that TEQ ⊆ BA and conjectured that every tournament contains a unique inclusion-minimal TEQ-retentive set, which was later shown to be equivalent to TEQ satisfying any one of a number of desirable properties for tournament solutions including stability and monotonicity (Laffond et al, 1993a;Houy, 2009a,b;Brandt et al, 2014;Brandt, 2011;Brandt and Harrenstein, 2011;Brandt, 2015). This conjecture was disproved by Brandt et al (2013), who have non-constructively shown the existence of a counterexample with about 10 136 alternatives using the probabilistic method. Since it was shown that TEQ satisfies the above mentioned desirable properties for all tournaments that are smaller than the smallest counterexample to Schwartz's conjecture, the search for smaller counterexamples remains an important problem.…”
Section: The Bipartisan Set and The Tournament Equilibrium Setmentioning
confidence: 99%